A membrane solid‐phase extraction method based on MIL‐53‐mixed‐matrix membrane for the determination of estrogens and parabens: Polyvinylidene difluoride membrane versus polystyrene‐block‐polybutadiene membrane. (28th July 2022) - Zhang, Yong; Wei, Kaifang; Wang, Litao; Gao, Guihua
Abstract: In this work, MIL‐53(Al), as an inorganic "filler" component, was embedded in polyvinylidene difluoride (PVDF) and polystyrene‐block‐polybutadiene (SBS) matrices to prepare two mixed‐matrix membranes (MMMs), using a simpler method than that previously reported. The PVDF and SBS membranes retained much of the properties of PVDF, SBS, and native MIL‐53(Al). The prepared MMMs were then placed in a vortex‐stirred sample solution to develop a membrane solid‐phase extraction method to extract estrogens and parabens, which were determined by high‐performance liquid chromatography with fluorescence detection. The extraction efficiencies of the two membranes were compared, with the PVDF membrane exhibiting superior performance. In addition, the PVDF membrane was more freestanding and flexible, and its preparation method was also more facile and simple. The extraction conditions were optimized, and the analytical method showed low limits of detection (0.005–0.18 ng/mL), good linearity, and high accuracy, with recoveries ranging from 90.7% to 102.5%. As a result, this membrane solid‐phase extraction method indicated its potential for application in aqueous sample pretreatment. For metal–organic framework–based MMM used in this method, in addition to being durable, freestanding, mechanically stable, and possessing a large area, it should also exhibit high metal–organic framework incorporation, good flexibility, and appropriate thickness and weight.